Thermal stability and dynamic mechanical properties of kenaf/bamboo fibre reinforced epoxy composites - Siew, Sand Chee; Jawaid, Mohammad; Sultan, Mohamed T. H. (North Carolina State University, 2017)
An increased awareness of environmental concerns has increased the need for innovation to produce high performance engineering materials with natural renewable resources. In this study, 3 types of natural fibre (mat form) reinforced epoxy composites were prepared by the hand lay-up method, namely, kenaf (K)/Epoxy, bamboo (B)/Epoxy, and bamboo charcoal (BC)/Epoxy. The thermal stability of the specimens was investigated by thermogravimetric analysis (TGA) and the dynamic mechanical properties. Viscous elastic behaviour of the specimens was investigated via a dynamic mechanical analyzer (DMA). The TGA results revealed that the BC/Epoxy composite showed the highest thermal stability compared to K/Epoxy and B/Epoxy with the highest initial and final decomposition temperature at 348 °C and 463 °C, respectively. It also showed the highest charcoal content at 11.5%. From the DMA results, the K/Epoxy composite showed better dynamic mechanical properties with the highest complex modulus (E*) strength and the lowest damping behaviour (peak height of Tan δ). The DMA analysis also revealed that the glass transition temperature of the composites fell between 60 °C to 90 °C. This preliminary study may give a new path to develop a novel hybrid composite that offers unique properties unachievable in a single material system.